2016
DOI: 10.1097/aog.0000000000001449
|View full text |Cite
|
Sign up to set email alerts
|

Using Bundled Interventions to Reduce Surgical Site Infection After Major Gynecologic Cancer Surgery

Abstract: Implementation of an evidence-based surgical site infection reduction bundle was associated with substantial reductions in surgical site infection in high-risk cancer procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 27 publications
(21 reference statements)
1
79
0
16
Order By: Relevance
“…One such strategy has been the introduction of "bundled interventions" in the perioperative time frame. Johnson et al 18 proposed the use of "bundled interventions" in gynecologic oncology patients undergoing laparotomies for surgical staging. In these context, bundled interventions include use of a chlorhexidine gluconate shower prior to surgery, chlorhexidine gluconate, or povidone iodine skin preparation in the operating room, prophylactic use of IV antibiotics are part of care for all the preoperative surgical patients at AKUH.…”
Section: Discussionmentioning
confidence: 99%
“…One such strategy has been the introduction of "bundled interventions" in the perioperative time frame. Johnson et al 18 proposed the use of "bundled interventions" in gynecologic oncology patients undergoing laparotomies for surgical staging. In these context, bundled interventions include use of a chlorhexidine gluconate shower prior to surgery, chlorhexidine gluconate, or povidone iodine skin preparation in the operating room, prophylactic use of IV antibiotics are part of care for all the preoperative surgical patients at AKUH.…”
Section: Discussionmentioning
confidence: 99%
“…Duke University and the Mayo Clinic have implemented bundled interventions following colorectal and gynecologic surgery with decreases in SSI rates from 50 to 80%. 13,14,16 Among high-risk gynecologic oncology patients, Novetsky et al implemented a five-part bundled intervention with reduction in the rate of SSI by 60%. 15 The intervention was also cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] To date, there is limited evidence regarding the effect of bundled initiatives on SSI rates following surgery for gynecologic malignancy. 15,16 Furthermore, the cost-effectiveness analyses of such initiatives have not been reported. The objective of this report is to describe the results and cost-effectiveness of a quality improvement initiative to reduce the rate of SSI within the Department of Gynecologic Oncology and Reproductive Medicine at a tertiary academic center specializing in cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, Using Bundled Interventions to Reduce Surgical Site Infection After Major Gynecologic Cancer Surgery, the investigators paired commonly used pre-interventions (patient education regarding infections, use of a chlorhexidine gluconate shower prior to surgery, chlorhexidine gluconate, and isopropyl alcohol skin preparation in the operating room, prophylactic use of cefazolin) with newly proposed intraoperative and postoperative interventions (sterile closing trays, and a shower with 4% chlorhexidine gluconate following dressing removal 24 hours post operatively). The authors showed a statistically significant decrease of overall SSI from 5.9% to 1.5% in patients with the newly proposed intraoperative and postoperative interventions [12]. In continuing with the bundled care for reduction of SSIs in gynecologic oncologic patients, Al-Niaimi et al and Chapman et al have identified perioperative glycemic control as an important aspect of the "bundle intervention".…”
Section: Site Infections In Gynecologic Oncologymentioning
confidence: 99%